2019
DOI: 10.1101/860239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deletion of mouseSetd4promotes the recovery of hematopoietic failure

Abstract: Key points:• Deletion of Setd4 in adult mice improved the survival from hematopoietic failure.• Setd4 deficiency sensitized HSCs to radiation, but improved bone marrow environment niche.• The study suggests that SETD4 as a potential inhibitory target to improve bone marrow niche function for recovery of bone marrow failure.Abstract: Acquired hematopoietic failure is commonly caused by therapeutic and accidental exposure to toxic agents to the bone marrow (BM). Efficient recovery from the BM failure is not only… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…This impairment leads to BM failure and often results in animal death, typically occurring within 1-3 weeks post-TBI. To test whether the SAP deletion confers a sensitization of the BM to radiation damage, we exposed sex-matched littermates to an 8 Gy TBI, a dosage known to cause mouse lethality due to BM failure (25). We observed that the KU70-ΔSAP mice were hypersensitive to IR.…”
Section: Resultsmentioning
confidence: 99%
“…This impairment leads to BM failure and often results in animal death, typically occurring within 1-3 weeks post-TBI. To test whether the SAP deletion confers a sensitization of the BM to radiation damage, we exposed sex-matched littermates to an 8 Gy TBI, a dosage known to cause mouse lethality due to BM failure (25). We observed that the KU70-ΔSAP mice were hypersensitive to IR.…”
Section: Resultsmentioning
confidence: 99%